Child and family outcomes of a long-term nurse home visitation programme: a randomised controlled trial. Issue 6 (23rd March 2011) - Kemp, Lynn; Harris, Elizabeth; McMahon, Catherine; Matthey, Stephen; Vimpani, Graham; Anderson, Teresa; Schmied, Virginia; Aslam, Henna; Zapart, Siggi
Abstract : Objective: To investigate the impact of a long-term nurse home visiting programme, embedded within a universal child health system, on the health, development and well-being of the child, mother and family. Design: Randomised controlled trial. Setting/participants: 208 (111 intervention, 97 comparison) eligible at-risk mothers living in a socioeconomically disadvantaged area in Sydney, booking into the local public hospital for confinement. Intervention: A sustained and structured nurse home visiting antenatal and postnatal parenting education and support programme. Control: Usual universal care. Main outcome measures: The quality of the home environment for child development (12–24 months), parent–child interaction and child mental, psychomotor and behavioural development at 18 months. Results: Mothers receiving the intervention were more emotionally and verbally responsive (HOME observation) during the first 2 years of their child's life than comparison group mothers (mean difference 0.5; 95% CI 0.1 to 0.9). Duration of breastfeeding was longer for intervention mothers than comparison mothers (mean difference 7.9 weeks; 95% CI 2.9 to 12.9). There was no significant difference in parent–child interaction between the intervention and comparison groups. There were no significant overall group differences in child mental, psychomotor or behavioural development. Mothers assessed antenatally as having psychosocial distress benefitted from the intervention across a number of areas. Conclusion: This sustained nurse home visiting programme showed trends to enhanced outcomes in many, but not all, areas. Specifically, it resulted in clinically enhanced outcomes in breastfeeding duration and, for some subgroups of mothers, women's experience of motherhood and children's mental development. Trial registration number: ACTRN12608000473369.